Phosphorus use in soybean in integrated production system under anticipation of phosphate fertilization (Revista Ciência Agronômica, 2020)
Conservation agriculture practices, such as integrated crop-livestock system (ICLS), can result in efficiency ofphosphorus use and, economic and environmental benefits. The higher nutrient cycling, deposited crop and animal residues inthe soil surface can promote the maintenance of soil fertility. Thus, the anticipated of phosphate fertilization may be a viablestrategy of fertilization for soybean crop, in this system. The objective of this work was to determine the yield, accumulationof P and phosphorus use efficiency (PUE) on the dry biomass and grains of the soybean crop, in an integrated crop-livestocksystem (ICLS) due to anticipated fertilization of sources and doses phosphates annually applied in the soil surface. Theexperiment was conducted over a period of five years, in Castro-PR, under a Typic Dystrudept, using a randomized blockdesign, in an incomplete factorial scheme (3×3+1), with four replications. The treatments consisted of three doses (60, 120 and180 kg ha-1 of total P2O5) plus absolute control, and three sources (triple superphosphate, rock phosphate – Arad and magnesiumthermophosphate) of P. The different sources no influenced and there were no interactions between P sources and doses forthe attributes: grain yield (GY), shoot dry mass (SDM), weight of thousand seeds (WTS), P accumulation in soybean (PAS),P concentration in soybean grains (PCSG), PUE and P in residual dry mass (PRDM). Linear increases were observed in GY,SDM, WTS, PCSG and PRDM and quadratic increases in PAS and PUE.